Economic cycles and self-employment: Synthetic cohort analysis for Greater Santiago; Ciclos económicos y trabajo independiente - Rodrigo Montero; Joaquín Pérez (Estudios de Economía, 2022)
Economic cycles affect both unemployment and the composition of employment, which can have an impact on the well-being of individuals if these changes in composition are involuntary or involve a decrease in the quality of employment. In this article, we study the relationship between economic cycles and self-employment, distinguishing between employers and own-account workers, through a synthetic cohort methodology using data for Chile. The results suggest that the proportion of employers is procyclical and that of own-account workers is countercyclical. This suggests that own-account employment is a refuge in times of crisis from the shortage of wage-based employment. This highlights the importance of designing public policies that would improve the conditions of self-employed workers.
Keywords: J08; J38; J39; 330; Self-employment; Employer; Own-account